Understanding the role and deployment of volunteers within specialist palliative care services and organisations as they have adjusted to the COVID-19 pandemic: A multi-national EAPC volunteer taskforce survey. (February 2023) - Walshe, Catherine; Pawłowski, Leszek; Shedel, Sophie; Vanderstichelen, Steven; Bloomer, Melissa J; Goossensen, Anne; Limonero, Joaquín T; Stoelen, Karen Sangild; Caraffa, Chiara; Pelttari, Leena; Scott, Ros
Background: Early indications were of a major decline in specialist palliative care volunteer numbers during COVID-19. It is important that ongoing deployment and role of volunteers is understood, given the dependence of many palliative care services on volunteers for quality care provision. Aim: To understand the roles and deployment of volunteers in specialist palliative care services as they have adjusted to the impact of COVID-19. Design: Observational multi-national study, using a cross-sectional online survey with closed and free-text option questions. Disseminated via social media, palliative care networks and key collaborators from May to July 2021. Setting/participants: Any specialist palliative care setting in any country, including hospices, day hospices, hospital based or community teams. The person responsible for managing the deployment of volunteers was invited to complete the survey. Results: Valid responses were received from 304 organisations (35 countries, 80.3% Europe). Most cared for adults only (60.9%), provided in-patient care (62.2%) and were non-profit (62.5%). 47.0% had cared for people with COVID-19. 47.7% changed the way they deployed volunteers; the mean number of active volunteers dropped from 203 per organisation to 33, and 70.7% reported a decrease in volunteers in direct patient/family facing roles. There was a shift to younger volunteers. 50.6% said this drop impacted care provision, increasing staff workload and pressure, decreasing patient support, and increasing patient isolation and loneliness. Conclusion: The sustained reduction in volunteer deployment has impacted the provision of specialist palliative care. Urgent consideration must be given to the future of volunteering including virtual modes of delivery, micro-volunteering, and appealing to a younger demographic.